Synthetic Utility of N-Acylbenzotriazoles - Yadav, Mangal S.; Gupta, Abhishek; Bose, Priyanka; Singh, Anoop S.; Mohapatra, Prabhu P.; Tiwari, Vinod K. (SynOpen, 2023)
N-Acylbenzotriazoles are valuable synthons in organic synthesis. They are particularly used as acylating agents and an alternative to acyl chlorides. They have been widely explored for a diverse range of applications. This review summarizes methods for the preparation of N-acylbenzotriazole derivatives and their diverse applications, in particular demonstrating their ability to serve as alternative acylating agents in organic transformations such as N-, O-, C-, and S-acylating agents for the convenient synthesis of a wide range of biologically important organic compounds. We also emphasize the synthesis of diverse compounds using benzotriazole ring cleavage (BtRC) methodology, including its pharmacophore study and some notable utilities as valuable starting materials, ligands, and intermediates in the field of organic synthesis.1 Introduction2 Synthesis of N-Acylbenzotriazoles3 Applications of N-Acylbenzotriazoles in Organic Synthesis3.1 N-Acylation Using N-Acylbenzotriazoles3.2 C-Acylation of Heterocycles Using N-Acylbenzotriazoles3.3 Preparation of β-Keto Esters and β-Diketones by Acylative Deacetylation3.4 N-Acylbenzotriazoles Used for the Preparation of Other Valuable Intermediates3.5 Benzotriazole Ring Cleavage (BtRC) Reactions4 N-Acylbenzotriazoles as Catalysts and Ligands5 Pharmacological Applications of N-Acylbenzotriazoles6 Conclusions and Future Outlook
Keywords: N-acylbenzotriazole; acylation; denitrogenative ring cleavage; acylative deacetylation; benzotriazole ring cleavage reactions